An electrically and magnetically responsive nanocomposite of GdPO4·H2O/P3HT/PLGA with electrical stimulation for synergistically enhancing the proliferation and differentiation of pre-osteoblasts. (28th October 2019) - Yan, Huanhuan; Li, Linlong; Wang, Yu; Huang, Jing; Wang, Zongliang; Shi, Xincui; Zhang, Peibiao
Abstract : The electric–magnetic responsive nanocomposite GdPO4 ·H2 O/P3HT/PLGA could enhance MRI signals, and synergistically accelerate proliferation and osteogenic differentiation upon electrical stimulation. Abstract : Although electroactive and magnetic biomedical composites have been proven respectively to promote bone regeneration, their associated biological effects have not been investigated. Herein, electroactive GdPO4 ·H2 O/P3HT/PLGA nanocomposites were prepared, which can enhance MRI and CT signals with different GdPO4 ·H2 O content (0.0, 1.0, 3.5, or 7.0 wt%). The morphology, hydrophilicity, magnetism, electroactivity and conductivity of the composites were characterized. Compared with PLGA, the composites exhibit good paramagnetism and electroactivity. The cell morphology and viability of pre-osteoblasts (MC3T3-E1 cell), their alkaline phosphatase (ALP) activity, calcium deposition, relative expression level of osteogenic genes, and MRI and CT imaging were studied. The proliferation of pre-osteoblasts was obviously increased on the GdPO4 ·H2 O (3.5 wt%)/P3HT/PLGA composite, and the composite containing 7.0 wt% GdPO4 ·H2 O significantly promoted osteogenic differentiation by increasing the ALP activity and calcium deposition, as well as the gene expression of Runx 2, OPN and OCN. Moreover, an enhanced effect was observed in osteogenic differentiation when the electroactive composites were coupled with electrical stimulation (ES) at a frequency of 100 Hz and electrical potential of 500 mV. In particular, OPN expression with GdPO4 ·H2 O (7.0 wt%) was up-regulated 3.0-fold compared to on glass with ES after 7 days. Besides this, the MRI and CT signals gradually enhanced with increasing GdPO4 ·H2 O content. Overall, the electroactive nanocomposite with traceability combined with ES can synergistically up-regulate cellular activity and may be a promising bone implant for bone repair and regeneration.